The Adaptive Management System for the Tasmanian Wilderness World Heritage Area — Linking Management Planning with Effectiveness Evaluation - Jones, Glenys (Adaptive Environmental Management, 2009)
This paper provides a 30 year retrospective on the development of the adaptive management system for the Tasmanian Wilderness World Heritage Area (Australia). It describes the historical background, key influences and stages that paved the way to establishment of adaptive management. It outlines how effectiveness monitoring, evaluation and reporting are integrated with the management plan for the Area to establish an ongoing adaptive management cycle. The chapter presents figures and tools for adaptive management, including 5 useful questions for guiding the integration of effectiveness monitoring, evaluation and reporting into management plans and programs. Strengths and weaknesses of the adaptive management system are discussed. Key lessons and insights distilled from this experience are offered, including the importance of planned monitoring of management effectiveness; the role of stakeholder assessments; and the factors that can assist in sustaining longterm strategic programs despite ongoing institutional change. The chapter concludes with suggestions for fostering an enabling environment for adaptive management.
Keywords: Adaptive Management; Management Intent; Reserve Management; World Heritage

Adaptive management of natural resources: theory, concepts, and management institutions. - Stankey, George H.; Clark, Roger N.; Bormann, Bernard T. (U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station, 2005)
This report reviews the extensive and growing literature on the concept and application of adaptive management. Adaptive management is a central element of the Northwest Forest Plan and there is a need for an informed understanding of the key theories, concepts, and frameworks upon which it is founded. Literature from a diverse range of ﬁelds including social learning, risk and uncertainty, and institutional analysis was reviewed, particularly as it related to application in an adaptive management context. The review identiﬁes opportunities as well as barriers that adaptive management faces. It concludes by describing steps that must be taken to implement adaptive management.

Adaptive Impact Management: An Integrative Approach to Wildlife Management - Riley, Shawn; Siemer, William; Decker, Daniel; Carpenter, Len; Organ, John; Berchielli, Louis (Human Dimensions of Wildlife, 2003)

Adaptive Management in Habitat Conservation Plans - Wilhere, George F. (Conservation Biology, 2002)
Habitat conservation plans (HCPs) allow incidental take of threatened or endangered species in exchange for conservation measures that minimize and mitigate such taking. Habitat conservation plans entail a compromise between regulatory certainty and scientific uncertainty. This compromise is controversial because many HCPs are thought to inadequately address scientific uncertainty. Adaptive management is the systematic acquisition and application of reliable information to improve natural resource management over time. Ideally, under adaptive management, conservation strategies are implemented as a deliberate experiment. This approach can establish cause-and-effect relationships and point the way toward optimal strategies. Adaptive management has been promoted as essential to management under uncertainty, but few HCPs incorporate genuine adaptive management. Habitat conservation plans will continue to lack adaptive management until certain conditions are met, such as acknowledgment that an HCP is a management hypothesis, landowner interest in improving biological outcomes, and sufficient financial resources. Economic incentives would encourage adaptive management in HCPs. Habitat conservation plan permittees might receive direct payments or tax deductions for reliable information that benefits a species. “Mitigation credits” could be awarded for information produced through adaptive management. In effect, habitat would be exchanged for information that benefits a species. Successful use of mitigation credits would depend on correctly valuing information and enforcement of the U.S. Endangered Species Act. Under a “precautionary polluter pays principle,” an HCP permittee would put up an environmental assurance bond. Portions of the bond are returned with interest as adaptive management demonstrates that environmental damages are unlikely to occur. Funds spent on adaptive management are funds unavailable for habitat protection, so limited financial resources may force a compromise between protecting habitat and acquiring knowledge.

Using Adaptive Management to Meet Conservation Goals - Franklin, Thomas M; Helinski, Ronald; Manale, Andrew (Fish and Wildlife Response to Farm Bill Conservation Practices, 2007)
Natural resource professionals should know whether or not they are doing an effective job of managing natural resources. Their decision-making process should produce the kind of results desired by the public, elected officials, and their agencies’ leadership. With billions of dollars spent each year on managing natural resources, accountability is more important than ever. Producing results is the key to success. Managers must have the necessary data to make enlightened decisions during program implementation—not just at the conclusion of a program. Adaptive management is described as an adapt-and-learn methodology as it pertains to implementing Farm Bill conservation practices. Four regional case studies describe how adaptive management is being applied by practicing fish and wildlife managers. Indicators were identified to monitor and evaluate contributions to fish and wildlife habitat for each of the case studies. Data collected at each stage of the studies were used to make mid-course adjustments that enabled leadership to improve or enhance ongoing management actions.

Adaptive Management: A Tool for Conservation Practitioners - Salafsky, Nick; Margoluis, Richard; Redford, Kent (Foundations of Success, 2001)

Adaptive Management, the Endangered Species Act, and the Institutional Challanges of New Age Environmental Protection - Doremus, Holly (Washburn Law Journal, 2001)

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives--rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations--they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making, Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Calibrating conservation: new tools for measuring success - Kapos, Valerie; Balmford, Andrew; Aveling, Rosalind; Bubb, Philip; Carey, Peter; Entwistle, Abigail; Hopkins, John; Mulliken, Teresa; Safford, Roger; Stattersfield, Alison; Walpole, Matt; Manica, Andrea (Conservation Letters, 2008)
Conservation practitioners, policy makers, and donors agree that there is an urgent need to identify which conservation approaches are most likely to succeed in order to use more effectively the limited resources available for conservation. While recently developed standards of good practice in conservation are helpful, a framework for evaluation is needed that supports systematic analysis of conservation effectiveness. A conceptual framework and scorecard developed by the Cambridge Conservation Forum help to address common constraints to evaluating conservation success: unclear objectives, ineffective information management, the long time frames of conservation outcomes, scarcity of resources for evaluation, and lack of incentives for such evaluation. For seven major categories of conservation activity, the CCF tools help clarify conservation objectives and provide a standardized framework that is a useful basis for managing information about project outcomes and existing conservation experience. By identifying key outcomes that can predict conservation success and can be assessed in relatively short time frames, they help to make more efficient use of scarce monitoring and evaluation resources. With wide application, the CCF framework and evaluation tool can provide a powerful platform for drawing on the experience of past and ongoing conservation projects to identify quantitatively factors that contribute to conservation success.
Keywords: Conservation effect; Conservation outcomes; Evaluation; Evidence-based conservation; Monitoring; conservation impact; framework; indicators; scorecard

Good Enough Governance Revisited - Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)

Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT